Intrinsic Pulse Widths of FRB 20121102A and Calculation of Broadening from Propagation and Instrumental Effects - Jia-Peng Wei; Yong-Feng Huang; Lang Cui; Xiang Liu; Jin-Jun Geng; Xue-Feng Wu (The Astrophysical Journal)
The pulse widths of fast radio bursts are always broadened due to the scattering of the plasma medium through which the electromagnetic wave passes. The recorded pulse width will be further affected by the radio telescopes since the sampling time and the bandwidth cannot be infinitely small. In this study, we focus on the pulse widths of at least 3287 bursts detected from FRB 20121102A as of 2023 October. Various effects such as the scattering broadening, the redshift-induced broadening, and the instrumental broadening are examined. At a redshift of 0.193, the pulse width is broadened by a factor of approximately 0.16 due to cosmological time dilation. It is found that the instrumental broadening only contributes a fraction of 10 ^−3 –10 ^−1 to the observed pulse width. The scattering broadening is even smaller, which constitutes a tiny fraction of 10 ^−5 –10 ^−2 in the observed pulse width. After correcting for these broadenings, the intrinsic pulse width is derived for each burst. The maximum and minimum pulse widths at different frequencies are highlighted. The intrinsic widths of most bursts are in a narrow range of 1–10 ms, which leads to a quasi-linear correlation between the fluence and the peak flux. Additionally, the mean value and the dispersion range of intrinsic pulse width are found to scale with the central frequency as ν ^−1.2±0.2 and ν ^−1.7±0.6 , respectively.